New Caffeic Acid Derivatives as Antimicrobial Agents: Design, Synthesis, Evaluation and Docking - Merlani, Maia; Barbakadze, Vakhtang; Amiranashvili, Lela; Gogilashvili, Lali; Poroikov, Vladimir; Petrou, Anthi; Geronikaki, Athina; Ciric, Ana; Glamoclija, Jasmina; Sokovic, Marina (Current Topics in Medicinal Chemistry, 2019)
Background: Phenolic acids (caffeic-, ferulic and p-coumaric acid) are widely distributed in the plant kingdom and exhibit broad spectrum of biological activities, including antimicrobial activity. Objective: The goal of this paper is the synthesis of some caffeic acid derivatives selected based on computer-aided predictions and evaluate their in vitro antimicrobial properties against Gram positive and Gram negative bacteria and also a series of fungi. Methods: In silico prediction of biological activity was used to identify the most promising structures for synthesis and biological testing, and the putative mechanisms of their antimicrobial action. The designed compounds were synthesized using classical organic synthesis methods. The antimicrobial activity was studied using microdilution method. Results: Twelve tested compounds have shown good antibacterial activity. Five out of twelve tested compounds appeared to be more active than the reference drugs ampicillin and streptomycin. Despite that all compounds exhibited good activity against all bacteria tested, the sensitivity of bacteria towards compounds in general was different. The evaluation of antifungal activity revealed that all compounds were more active than ketoconazole, while seven compounds (2, 3, 4, 5, 7, 8 and 12) appeared to be more active than bifonazole. Docking results indicate that gyrase inhibition is the putative mechanism of antibacterial action while the inhibition of 14α-demethylase may be responsible for antifungal action. Prediction of cytotoxicity by PROTOX showed that compounds are not toxic (LD50 1000-2000 mg/kg). Conclusion: Thirteen compounds, from which six are new ones, were synthesized, and twelve compounds were tested for antimicrobial activity. The studied compounds appeared to be promising potent and non-toxic antimicrobials, which could be considered as leads for new pharmaceutical agents.
Keywords: Caffeic acid derivatives